P490 Incidence and 5 years survival rates of childhood cancer diagnosed less than 1 year old in Ireland 2007–2017. (June 2019) - Wong, Jsun Loong; Clinton, Frieda; Carroll, Maria; Malone, Andrea; O'Marcaigh, Aengus; Smith, Owen Patrick; Pears, Jane; Capra, Michael; Owens, Cormac
Abstract : Introduction: Childhood cancer is the second commonest cause of death in children in developed countries. Childhood cancer survival rates has improved over the last decade with the advancement of diagnostic procedures and continuous improvement of multimodal treatment strategies. According to the National Cancer Registry of Ireland, an average of 137 cancers were diagnosed per year in children under the age of 15 between 1994 and 2014. The 5-year overall survival rate for this entire cohort was 81%. It is well documented that survival rates in paediatric oncology vary depending on specific cancer diagnosis, age of the patient at diagnosis and disease stage. Aim: We describe the incidence of cancer in very young children and the influence of age on outcome in children diagnosed with cancer in Ireland under the age of 1 between 2007–2017. Method: Data were extracted from the database of the National Children's Cancer Service (NCCS) based at Our Lady's Children's Hospital, Dublin. The data presented refer to the International Classification of Childhood Cancer (ICCC) version 3 with the inclusion of Langerhans Cell Histiocytosis (LCH). Result: 185 patients were diagnosed with paediatric cancer under the age of 1 at the time of their initial diagnosis. 159 (85.5%) patients were diagnosed with solid tumours or LCH. 86 (46.5%) were male. The average age at diagnosis was 5.24 (range 0–12) months. 19 (10.3%) patients were diagnosed following an abnormal antenatal scan. The most common cancers diagnosed were neuroblastoma (22.7%), CNS tumours (19.5%) and leukaemia (13.5%). 158 (85.5%) patients received treatment. 124 (78.4%) patients received chemotherapy as part of their treatment. 20 (12.7%) patients received radiotherapy. The mean age for radiotherapy was 1.35 years (range 0.17–4). 18 (9.7%) patients received stem cell transplant/rescue. The cumulative overall survival rate at 5 years is 80%. CNS tumours have the worst prognosis followed by leukaemias. 35 (18.9%) patients have relapsed during follow up, and 20 are alive in follow-up. Conclusion: Incidence rates of specific paediatric cancer types vary according to the age at diagnosis. There is no difference in survival rates between children diagnosed with cancer under 1 year of age and older children. Outcomes at the NCCS compare favourably with international standards.